Fabrication and properties of ternary aluminium-magnesium-zinc alloy filled with polypropylene - Teoh, Ai Ling (School of Materials Engineering, 2012)
The objectives of this research are: 1) To fabricate the ternary Al-Mg-Zn alloy filled with PP; 2) To study the effect of PP addition on the microstructure of ternary Al-Mg-Zn alloy; 3) To study the effect of PP addition on the physical and mechanical properties of ternary Al-Mg-Zn alloy.